Penitential punishment and purgatory: a drama of purification through pain - Kirakosian, Racha (Punishment and Penitential Practices in Medieval German Writing, 2018)
Keywords: 👤 christina of hane

Musical heaven and heavenly music: at the crossroads of liturgical music and mystical texts - Kirakosian, Racha (Viator: Medieval and Renaissance Studies, 2017)
Keywords: 👤 christina of hane

Rhetorics of Sanctity: Christina of Hane in the Early Modern Period with a Comparison to a Mary Magdalene Legend - Kirakosian, Racha (Oxford German Studies, 2014)
This study presents the particular case of the medieval mystic Christina of Hane in the Early Modern transmission to uncover the dynamics of sanctity across traditional period boundaries. It discusses the interest of copying and transmitting the Life of this local saintly figure with a legend on Mary Magdalene’s conversion in the sixteenth century. Christina of Hane’s medieval Life becomes refashioned in a seventeenth-century Flemish text that addresses the religious needs of its time, stressing apolitical forms of devotion such as prayers for the souls in purgatory.
Keywords: 👤 christina of hane

Which is the Greatest - Kirakosian, Racha (Medieval Mystical Theology, 2014)
This paper deals with the medieval theological debate on the primacy of knowledge, love, or enjoyment of God by comparing the biography of the Premonstratensian nun Christina of Hane with the German mystical writings of the Dominican preacher and scholar Meister Eckhart. It shows the ways in which female vernacular thought engaged with a primarily scholastic and male-dominated debate and suggests a performative understanding of the female mystical account. Challenging existing presumptions about Christina’s mystical biography as being inconsistent and composed by several authors, the results of this research demonstrate to what extent the text can still be considered cohesive when discarding gender specified authorial conceptions which cannot be determined in this case.
Keywords: 👤 christina of hane